Behavioral service solutional steps in the context of sexual harassment issues in higher education - Maulida, Intan Dewi (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2017)
This paper is an exploratory study of the polemic of sexual abuse in college. Academic community as an important factor in the context of homo-social, has the potential to grow in al-ghadabiyah and al-syahwaniyah. If a person is not able to control himself in a good direction, then lust will lead to negative direction and trigger mental illness conditions such as sexual harassment behavior, and vice versa. Behavioral service as a catalyst requires specifically earthing to overcome sexual harassment behavior by adaptation into the college curriculum. Behavioral conceptualization service there are two types of preventive and curative that the system works differently, but in practice has the same goal that is, to lead the students to actualize themselves in accordance with the ability and the scientific basics. The key to success behavioral service lies in the synergy of the relationship between counselor and counselee who gave birth to three principles namely, awareness, openness, and confidentiality.